REKONSTRUKSI STANDAR PENERAPAN PEMAAFAN HAKIM GUNA MENJAMIN KEPASTIAN DAN KEADILAN PEMIDANAAN - Andi Rosadi Hamri; Mahendra Putra Kurnia; Ivan Zairani Lisi (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to analyze the application of the concept of judicial forgiveness (rechterlijk pardon) as stipulated in Law Number 1 of 2023 concerning the National Criminal Code (KUHP). The primary focus of the study is to examine the legal rationale for granting this pardon authority and its concept in supporting substantive justice in Indonesia. The research method used is normative juridical with a statutory and conceptual approach. The results indicate that judicial forgiveness is an important instrument for correcting injustice resulting from the application of the rigid principle of legality. Through Article 54 of the National Criminal Code, judges have a legal basis for not imposing a sentence even if the defendant's guilt is proven, taking into account the minor nature of the act and the humanitarian aspects. This concept reinforces the shift in Indonesian criminal law towards a restorative and humanistic direction.